Anisakis simplex (Rudolphi, 1809) Dujardin 1845 - Arai, Hisao P.; Smith, John W. (Zenodo, 2016)
* Anisakis simplex (Rudolphi, 1809) Dujardin, 1845 ( sensu lato ) Includes * Anisakis simplex B and C auct Description (after Beverley-Burton et al. 1977, J. W. Smith 1983, and J. W. Smith & Wootten 1984b). With characteristics of the genus. Off-white in colour, L3 lie in capsules coiled like a watch-spring. From 8.8 to over 30 long. Cuticle usually transversely striated near anterior and posterior extremities. Mouth triangular with bilobed dorsal lip and two bilobed ventro-lateral lips, each lip with pair of indistinct papillae. Anteroventrally projecting boring tooth located ventral to mouth (Fig. 73 A,B,C). Excretory pore between ventro-lateral lips with single duct passing up from excretory cell (Fig. 73 A,B). Dorsal oesophageal gland extends just anterior to nerve ring. Two small ventro-lateral glands near posterior end of oesophagus. Oesophagus comprises preventriculus and ventriculus. Ventral side of ventriculus slightly longer than dorsal side (Fig. 73 A). Intestinal-rectal valve short, lined externally by four epithelial cells. Three rectal glands, two dorsal and one ventral. Tail rounded with retractable mucron (Fig. 73 D). Length of preventriculus and ventriculus linearly related to total body length. Mean length of thirty L3 from one fish host was 22.6 (range 18.0–22.9), mean preventriculus length 1.94, and mean ventriculus length 0.89. Sites: body cavity, alimentary tract, mesenteries, musculature Hosts: Acipenser transmontanus (33); Alosa aestivalis (57); Alosa pseudoharengus (6, 57); Amblyraja radiata (49); Ammodytes dubius (28, 49); Argentina silus (49); Atheresthes stomias (76); Boreogadus saida (70, 73, 83); Brosme brosme (49); Clupea harengus (2, 4, 6, 7, 19, 25, 30, 32, 34, 35, 41, 54, 65, 68, 70, 72, 74); Clupea pallasi (8, 11, 12, 13, 73); Coregonus huntsmani (83); Cyclopterus lumpus (49); Gadus macrocephalus (74); Gadus morhua (17, 27, 28, 29, 36, 41, 42, 48, 49, 55, 60, 61, 64, 70, 73, 80, 82); Gadus macrocephalus (65); Glyptocephalus cynoglossus (28, 36, 49, 65); Hemitripterus ...